Computer Science & Technology Series : XIX Argentine Congress of Computer Science. Selected papers - Finochietto, Jorge Raúl (2014)
CACIC’13 was the nineteenth Congress in the CACIC series. It was organized by the Department of Computer Systems at the CAECE University in Mar del Plata. The Congress included 13 Workshops with 165 accepted papers, 5 Conferences, 3 invited tutorials, different meetings related with Computer Science Education (Professors, PhD students, Curricula) and an International School with 5 courses. CACIC 2013 was organized following the traditional Congress format, with 13 Workshops covering a diversity of dimensions of Computer Science Research. Each topic was supervised by a committee of 3-5 chairs of different Universities. The call for papers attracted a total of 247 submissions. An average of 2.5 review reports were collected for each paper, for a grand total of 676 review reports that involved about 210 different reviewers. A total of 165 full papers, involving 489 authors and 80 Universities, were accepted and 25 of them were selected for this book.